2021
DOI: 10.1186/s12888-021-03066-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and its associated factors of depressive symptoms among Chinese college students during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has caused a mental health crisis around the world. The psychological health of college students also faces great challenges. This study aimed to investigate the prevalence and the related factors of depressive symptoms among Chinese college students. Methods This online cross-sectional survey was conducted via Wenjuanxing platform from March 3–15, 2020 and received 1681 effective questionnaires. Each questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 43 publications
(52 reference statements)
10
52
0
2
Order By: Relevance
“…The present results emphasize the importance of strong social support to prevent mental health disorders, which has been previously demonstrated (22,30,31). Positive social support can not only buffer the effect of uncertainty and stress related to the pandemic on depressive symptoms (30,32), but also increase the feeling of social connectedness, which could protect students against depressive symptoms (12).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present results emphasize the importance of strong social support to prevent mental health disorders, which has been previously demonstrated (22,30,31). Positive social support can not only buffer the effect of uncertainty and stress related to the pandemic on depressive symptoms (30,32), but also increase the feeling of social connectedness, which could protect students against depressive symptoms (12).…”
Section: Discussionsupporting
confidence: 79%
“…A previous review shows that support from parents was the most important factor protecting against depression in Western children and adolescents (29). During the pandemic, this protective effect of social support on depression was consistently found in college students (15,22,(30)(31)(32). Furthermore, due to the strategy of staying at home, time spent on electronic devices increased markedly (33).…”
Section: Introductionmentioning
confidence: 97%
“…During the pandemic of COVID-19, previous related studies showed that 22.4–35.5% medical students reported depressive symptoms ( 24 , 25 ) and 22.1–28% reported anxiety symptoms ( 24 , 26 ). Among general University students, depressive symptoms ranged from 12.2 to 56.8% ( 27 , 28 ), and anxiety symptoms ranged from 7.7 to 15.43% ( 27 , 29 ). An online mental survey targeting different populations showed the prevalence of depression, anxiety, and stress-related symptoms was 50.7, 44.7, and 73.4%, respectively ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the large number of stressors related to infectious disease is a risk factor in predicting individual psychological symptoms during SARS (9). In addition, the risk perception of being infected with COVID-19 disease is the common response by general population during the pandemic (10,11). The risk perception model of health suggests that stressful events related with infectious disease have indirect negative effects on individual mental health by increasing individuals' perceived risk of being infected with diseases (12).…”
Section: Introductionmentioning
confidence: 99%